PROFIL ASAM LEMAK OMEGA-3, OMEGA-6, PERKEMBANGAN MENTAL DAN PSIKOMOTOR ANAK KEP BERAT DAN GIZI BAIK - Astuti Lamid; Sri Muljati; Lies Karyadi; Komari Komari; Sri Murni Prastowo; Slamet Budiyanto (Persagi, 1999)
The Profile of Omega-3 and Omega-6 Fatty Acids, Mental and Psychomotor Development of Severe Malnutrition and Well-Nourished Children.It has been carried out the study to find the profile of omega-3, omega-6, mental and psychomotor development of severe malnutrition and well-nourished children. This study was cross-sectional study conducted on children suffering from severe malnutrition at Nutrition Clinic, Nutrition Research and Development Center, Bogor and well-nourished children from the same environment, age and sex. Thirty children of 6-24 months were collected consisting of 15 severe malnutrition children and 15 well-nourished children. Data collected were level of omega-3, omega-6 in blood, mental and psychomotor development, anthropometry, food consumption, food frequency and social economic conditions of the family. Results showed that the level of omega-3 and omega-6 of the severe malnutrition children were lower than those of the well-nourished children. The mental and psychomotor development measured with MDI and PDI scores for the severe malnutrition children were lower compared to the well-nourished children. Non-parametric analysis showed that the level of omega-3, omega-6, MDI and PDI of the severe malnutrition children was significantly difference (p<0,01) compared to the wll-nourished children. The ratio between level of omega-3 and omega-6 for the severe malnutrition children was less than 1/4. Coefficient correlation of ratio omega-3 and omega-6 with MDI and PDI was found 0,458 and 0,581 (p<0,01).Keywords: omega-3, omega-6, MDI, PDI, severe malnutrition